Qualidade de imagem em exame de colangiopancreatografia por ressonância magnética: estudo entre suco de açaí e contraste comercial - Pinho, Katia Elisa Prus (2019)
Magnetic resonance cholangiopancreatography (MRCP) exams make use of negative contrasts to identify and visualize the images of the pancreas and gallbladder. In this work, we compare the image quality obtained with 2 protocols using oral contrast agents in MRCP exams, one developed and employing a chosen natural juice and another employing a commercial contrast. Initially, phantom studies were performed with several juices in order to choose one that presented adequate properties from the perspective of the MRCP exam. Subsequently, metal constituents of the juices were investigated and a sensorial analysis was performed between juice and commercial contrast. A clinical study protocol was developed, which was applied in 64 patients from a University Hospital of Curitiba-PR. The patients underwent MRCP exams on two consecutive days in a Diagnostic Clinic. On the first day they received commercial contrast and in the second, the juice chosen. Two radiologists (A1 and A2) evaluated the MRCP images and completed a form, analyzing the quality of the images and classifying them through a score (1 to 4). Image J® software was also used to quantitatively evaluate the images by comparing them with the medical evaluation. The results obtained in phantom have determined acai juice as one of the best options for the MRCP exams. In the sensory analysis, the commercial contrast scores remained between 5 (25%), 6 (21.9%) and 7 (32.8%) and with natural juice they prevailed in 6 (37.5%) and 7 (46.9%). In the evaluation of the images of the 1st day, A1 kept the score at 3.52 and A2 at 3.27. On day 2, A1 provided 3.44 and A2 3.38. Regarding the quality of the commercial contrast images, both A1 and A2 considered that in 96.9% of patients, this was adequate. Regarding the efficacy of natural contrast, for A1 in 62 patients (96.9%), it was adequate. For A2, in 60 patients (93.8%), it was effective. Applying Image J® on areas of interest in MRCP images, it was obtained a correlation coefficient of 0.986 between average curves of contrasts A and B. Thus, the natural juice presented quality compatible with the commercial contrast in MRCP images, both by medical analysis and Image J® software, besides excellent acceptance for all patients, being affordable and totally natural.